The Complementarity of Improving Quality of Life and Reducing Environmental Footprints in Urban Spaces: The Argument for ‘Hedonistic Sustainability’ - Mohtadi, Tara (Consilience, 2016)
In recent decades, the phenomena of urbanization and globalization have transformed cities into of technology, innovation, wealth and human capital. Cities have become spaces of high environmental destruction, and concurrently, frontrunner of climate change adaptation and mitigation strategies. The urban landscape consists of a complex network of actors, requiring an integrative and adaptive approach to be taken when considering sustainability and environmental soundness. Much of the sustainability discourse focuses on functionality, sacrifice, and often, individual lifestyle changes. This paper seeks to challenge that perspective by proposing that a collectivistic approach with implications of prosperity can optimize urban adaptation, remediation, and expansion amidst the agglomerations threat of climate change.